IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN STUDI AL QU’AN HADIST DI MTs. FATHUSSALAM - Abdulloh Hannan Mas’sum (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Education is one of the important aspects in shaping the character and knowledge of the younger generation. One of the subjects that has a strategic role in Islamic education is Hadith Studies. However, it is often found that conventional learning methods are less effective in improving students' understanding of hadith material. This raises the need to implement more innovative and interactive learning methods, one of which is the problem-based learning (PBL) learning model.This study used quantitative methods with a pseudo-experimental design, The study population was all students at MTs. The study population was all students at MTs Fathussalam, and the sample was taken using purposive sampling technique.The data obtained were analyzed descriptively to describe the profile of students' understanding before and after treatment.The inferential analysis used a t-test to test the research hypothesis regarding the difference in students' understanding between the experimental and control classes.The results of the author's observations in the field show that students can collaborate with their group members, for example by sharing and collaborating on tasks during classroom presentations. Collaboration helps students develop a critical attitude, and dialogue with friends helps students develop the knowledge they gain.First, Al-Quran Hadith teachers at MTs. Fathussalam use problem-based learning models to create a meaningful learning environment for students. Second, the application of problem-based learning model affects the internalization of students' Islamic values. The effects of the learning process using the PBL model are: Students are able to believe and recognize the truth of Islamic teachings and values.